2022
DOI: 10.31605/eduvelop.v5i2.1460
|View full text |Cite
|
Sign up to set email alerts
|

The Show must go on: How Students’ Perception on Online Learning in Bojonegoro

Abstract: Pandemic covid 19 spreads rapidly. Due to its quick breaks, a lot of countries decided to change some daily routine activies. One of affected aspects is education. Face to face learning has to be turned out into online learning in any level of schools. This present reseach aims to investigate and survey the students’ perception on online learning and what online fatlform mostly used by the students. This research is classified as qualitative research.  This research took 74 participants. The data was obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This finding support the previous study conducted by Lestarir and Fatoni (2022), that concluded online learning is challenging for students. In this case, they found problems during online learning such as internet connection and accessibility are complicated and their smartphone with less memory devices.…”
Section: Discussionsupporting
confidence: 92%
“…This finding support the previous study conducted by Lestarir and Fatoni (2022), that concluded online learning is challenging for students. In this case, they found problems during online learning such as internet connection and accessibility are complicated and their smartphone with less memory devices.…”
Section: Discussionsupporting
confidence: 92%
“…Dealing with technology, it is essential part in teaching and learning. It helps teaching and learning keep going both in synchronous and asynchronous mode (Lestari & Fatoni, 2022). In other word, technology and learning are essential parts in educational aspect.…”
Section: Introduction *mentioning
confidence: 99%
“…According to Rakhmat (1999), perception is the experience of things, events, or relationships formed through inference and interpretation of messages. Lestarir and Fatoni (2022) stated that perception is experiencing an event, object, or time by receiving and processing information. Teachers and students have differing opinions on this new educational and video conferencing system (Farhah Jatnika et al, 2021).…”
Section: Introductionmentioning
confidence: 99%